A mixed methods study of Canadian adolescents' perceptions of health. Issue 1 (1st January 2016) - Michaelson, Valerie; Pickett, William; Vandemeer, Eleanor; Taylor, Brian; Davison, Colleen
Abstract : Health perceptions adopted during childhood lay foundations for adult health trajectories and experiences. This study used a sequential mixed methods design to generate new evidence about child perceptions of health in two samples of Canadian children. A core qualitative study was followed by a complementary quantitative analysis to aid interpretation. Generational theory was used as a lens through which to interpret all data. Findings suggested that good health is perceived as customized and subjective. The strengths and liabilities of these perceptions are discussed, as well as implications for health promotion and prevention strategies. Through intentional consideration of the perspectives of this population group, this study makes both empirical and theoretical contributions to appreciating how cultural environments shape health perceptions.